2017
DOI: 10.4049/jimmunol.1601662
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Motile Sperm Domain–Containing Protein 2 as Regulator of Human Monocyte Migration

Abstract: Binding of chemokines to their cognate receptors on monocytes instigates a cascade of events that directs these cells to migrate to sites of inflammation and cancerous tissues. Although targeting of selected chemokine receptors on monocytes exhibited preclinical efficacy, attempts to translate these studies to the clinic have failed thus far, possibly due to redundancy of the target receptor. We reveal that motile sperm domain–containing protein 2 (MOSPD2), a protein with a previously unknown function, regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…S. agalactiae derived self-antigen, Lmb mimicked MOSPD2 was obtained after rigorous screening procedures explained in the previous study [1] . Recently, a group has shown the functional identification of MOSPD2 protein in the myeloid cells [89] . According to them, MOSPD2 is strictly localized on the plasma membrane of CD14+ ​human monocytes and neutrophils and hence, regulates monocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…S. agalactiae derived self-antigen, Lmb mimicked MOSPD2 was obtained after rigorous screening procedures explained in the previous study [1] . Recently, a group has shown the functional identification of MOSPD2 protein in the myeloid cells [89] . According to them, MOSPD2 is strictly localized on the plasma membrane of CD14+ ​human monocytes and neutrophils and hence, regulates monocyte migration.…”
Section: Discussionmentioning
confidence: 99%
“…By tethering the ER and other organelles, MOSPD2 most likely functions in intracellular exchanges and communication. MOSPD2, which is expressed on the plasma membrane of human monocytes, was explored for its potential to regulate cancer cell migration and metastasis [ 55 , 56 ]. In our research, MOSPD2 had low expression in EBV-miR-BART-22 overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…MOSPD2 is also found in neutrophils, but not in lymphocytes. It is revealed that MOSPD2 is critical in regulating the inflammatory monocyte and neutrophil migration without activating ligands [ 103 ]. The monocyte from blood can rise macrophage in CNS, which is dominant in demyelination [ 104 ].…”
Section: Discussionmentioning
confidence: 99%